Appalachia : the voices of sleeping birds - Rylant, Cynthia; Moser, Barry (New York : Veryager Books, 1991)
Text and illustrations explore the countryside and people of Appalachia.
Keywords: Appalachian Region, Southern -- Description and travel -- Juvenile literature; Appalachian Region, Southern -- Social life and customs -- Juvenile literature; Appalachian Region, Southern